Exploring the relationship between self-efficacy and aggression in a group of adolescents in the peri-urban town of Worcester - Willemse, Michele (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Psychology))--University of Stellenbosch, 2008.